Online or Face-to-Face Learning? College Students’ Perceptions in the Aftermath of the COVID-19 Pandemic - Morera Quesada, Georgina (2023)
Online learning has been available for more than two decades, but it was not up until the COVID-19 pandemic that most educational institutions had to adopt it in early 2020. This major shift brought about a large number of complications for students; thus, most studies show that students prefer face-to-face learning over online education. Our study attempts to increase our understanding of the different nuances related to and about the effect of online learning during the COVID-19 pandemic on a particular group of higher-education students from a small regional campus. We conducted an online survey and collected data on students that had entered the university before 2020, to ensure that they had experienced both face-to-face and online learning. We collected students’ sociodemographic data, their online learning conditions, perceived advantages and disadvantages of online compared to face-to-face learning, and general perceptions about their learning process. The results show that students faced some of the most typical difficulties identified in previous studies: a significant increase in class workload, poor quality of internet connection, and an increase in a sense of isolation and loneliness, among others. Yet despite these difficulties, students had an overall positive perception of online learning and the majority agreed that this learning modality should be maintained. This positive perception may be related to various difficulties faced during regular face-to-face learning, such as steep commuting costs and the emotional toll of becoming separated from the family.